Dream town - Baldacci, David (New York : Grand Central Publishing, 2022)
"Private Investigator and World War II veteran Aloysius Archer heads to Los Angeles, the city where dreams are made and shattered, and is ensnared in a lethal case."--
Keywords: Archer, Aloysius -- (Fictitious character) -- Fiction; Private investigators -- Fiction; Murder -- Fiction; Ex-convicts -- Fiction; Veterans -- Fiction; Murder -- Investigation -- Fiction; California -- Fiction; Los Angeles (Calif.) -- Fiction; Thrillers (Fiction).; Detective and mystery fiction